A Systematic Review Lateral Repositioning for Preventing Pressure Ulcers in Stroke Patients: Lateral Repositioning for Preventing Pressure Ulcers in Stroke Patients: A Systematic Review - Winardi, Aswedi; Arafat, Rosyidah (Alta Dharma Publisher, 2024)
Introduction: Pressure ulcers (PU) are a common complication among stroke patients, especially those with limited mobility. Proper nursing interventions, such as regular lateral repositioning, play a crucial role in preventing these injuries. However, the optimal angle and frequency of repositioning remain subjects of ongoing research.Objective: This systematic review aims to synthesize evidence on the effectiveness of various lateral positions and repositioning intervals in reducing the risk of PU in stroke patients. Method: This review follows PRISMA guidelines. Literature searches were conducted using databases such as PubMed, ScienceDirect, and Google Scholar, focusing on studies investigating lateral positioning interventions for stroke patients. Inclusion criteria consisted of studies published in English and Indonesian, with no publication year restrictions, covering any stroke subtype. We framed the research questions using PICO elements and analyzed the selected articles with the CASP checklist, classifying them based on levels of evidence and recommendation strength. Results: Seven studies were included in the final analysis, with four conducted in Indonesia and three from international sources. The findings indicate that a 30° lateral tilt is more effective than a 90° angle in preventing PU. Additionally, repositioning every 2–3 hours significantly reduces the risk, while repositioning every 3–4 hours presents a cost-effective alternative without increasing risk. An economic analysis highlighted substantial savings with repositioning every 3 hours compared to every 2 hours.Recommendation: Lateral repositioning at a 30° angle and 3–4-hour intervals provides an optimal balance between effectiveness and cost-efficiency in preventing PU among stroke patients. Further research with larger sample sizes and robust designs is recommended to strengthen the evidence base.